Evaluasi Kapasitas Dan Optimalisasi Apron Pada Bandar Udara (Studi Kasus : Bandar Udara Sultan Syarif Kasim II Kota Pekanbaru, Riau) - M. Fajar Anwika; Ari Sandhyavitri; Alfian Malik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Sultan Syarif Kasim II Airport has annually experienced an increase in the number of passengers and the number of aircraft operating based on data from 2010 to 2018. Therefore, it is necessary to evaluate and optimize the apron. The purpose of this study is to determine the peak hour aircraft movements, project the need for parking stands and optimize for the existing year (2020) and the plan year, namely 2030 and 2035, using aircraft data B 737-900 as the largest planned airport aircraft. Forecasting the movement of the number of aircraft is carried out using the regression method. The results of the analysis in 2030 and 2035 the apron capacity of SSK II Airport has exceeded the existing capacity, because the current apron capacity at SSK II Airport is 12 parking stands with an area of 476 x 110 m. The area and capacity of the apron required in 2030 are 18 parking stands with an apron area of 710 x 150 m and for 2035, it is 20 parking stands with an apron area of 780 x 150 m. Keywords: Apron, Parking Stand, Optimization, Regression